2005
DOI: 10.1128/aac.49.8.3554-3557.2005
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanism of Resistance to Oxazolidinones, Macrolides, and Chloramphenicol in Ribosomal Protein L4 of the Pneumococcus

Abstract: Two clinical Streptococcus pneumoniae isolates, identified as resistant to macrolides and chloramphenicol and nonsusceptible to linezolid, were found to contain 6-bp deletions in the gene encoding riboprotein L4. The gene transformed susceptible strain R6 so that it exhibited such resistance, with the transformants also showing a fitness cost. We demonstrate a novel bacterial mechanism of resistance to chloramphenicol and nonsusceptibility to linezolid.Macrolide resistance in Streptococcus pneumoniae is predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
104
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 33 publications
2
104
0
3
Order By: Relevance
“…Instead, positions 1743 and 2503 were mutated and three copies of the domain V 23S rRNA had the A2503G mutation at 16 mg/mL, while the fourth copy was mutated when cells reached a MIC of 32 mg/mL (Supplemental Table 2). Small deletions in the 50S ribosomal protein L4 were observed in clinical strains of S. pneumoniae with decreased susceptibility to linezolid (Wolter et al 2005). It is salient to point out that in mutant 1974M2, whole-genome sequencing revealed that the L4 protein is mutated to G71R, a conserved region of L4.…”
Section: Mutations In Known Loci Associated With Linezolid Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Instead, positions 1743 and 2503 were mutated and three copies of the domain V 23S rRNA had the A2503G mutation at 16 mg/mL, while the fourth copy was mutated when cells reached a MIC of 32 mg/mL (Supplemental Table 2). Small deletions in the 50S ribosomal protein L4 were observed in clinical strains of S. pneumoniae with decreased susceptibility to linezolid (Wolter et al 2005). It is salient to point out that in mutant 1974M2, whole-genome sequencing revealed that the L4 protein is mutated to G71R, a conserved region of L4.…”
Section: Mutations In Known Loci Associated With Linezolid Resistancementioning
confidence: 99%
“…In addition to mutations in the 23S rRNA, a 6-bp deletion in the ribosomal protein L4 has been described in two clinical isolates of S. pneumoniae that were resistant to chloramphenicol and not susceptible to linezolid (Wolter et al 2005). Recently, an integrated plasmid 23S rRNA methyltransferase coded by the cfr gene (for chloramphenicol-florfenicol resistance) was shown to confer resistance to linezolid in S. aureus (Toh et al 2007;Mendes et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The number of rRNA genes mutated depends on the dose and duration of linezolid exposure and has been shown to influence the level of linezolid resistance (3,15). Also, a linezolid-resistant isolate of S. pneumoniae was found to contain a 6-bp deletion in the gene encoding riboprotein L4 (30).…”
mentioning
confidence: 99%
“…Therefore, the growth of E. coli and S. oneidensis was not markedly affected, which indicated that the antibacterial activity of CAP was largely eliminated by the MFC. CAP was first transformed to the CAPacetyl and AMCl2, which involved changes to its functional groups (Jiang et al, 2016;Wolter et al, 2005). Moreover, the aromatic structure of these two CAP metabolites was destroyed via a meta-cleavage pathway.…”
Section: Antibacterial Activity Of Cap Degradation Productsmentioning
confidence: 99%